Foresting Entrepreneurial Spirit of Santri With Santripreneur Academy Program: Study on Pesantrenpreneur Mukmin Mandiri - Bagus Setiawan, Heri Cahyo; Hidayat, Nur; Kurniawan, Aries; Komara, Beni Dwi (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
Currently, pesantren must be able to produce graduates with various skills because not all outputs or alumni become scholars or kiai. One of the educations that are provided for students is entrepreneurship. This study will present an overview of how the efforts of Islamic boarding schools not only provide students with understanding religious knowledge (tafqquh-fiddin), but are taught about skills that can have economic value with entrepreneurship education. The Mukmin Mandiri Islamic Boarding School in Sidoarjo is the object of this research, in which students are taught religious knowledge and at the same time understand economics and business through the Santripreneur Academy program. The purpose of exploring and exploring the role of the entrepreneurship education program which is named the Santripreneur Academy program is interesting to answer the research question